What’s inside the net? insights into fish bycatch diversity in the Antarctic krill fishery - María Lorena Romero Martínez; William D. K. Reid; Martin A. Collins; Katia Lizeth Treviño Cuellar; William P. Goodall-Copestake; James M. Clark; Benedict Viney; Susan Gregory; Kate Owen; Philip R. Hollyman (Polar Biology, 2026)
An ecosystem-based approach to fishery management requires, inter alia, knowledge of fishery impacts on both target and non-target species, as well as the wider ecosystem. To support management of the Antarctic krill fishery, we present a robust reference dataset for identifying fish species caught as bycatch. By combining morphological and molecular taxonomic identification, 53 fish species in 44 genera and 11 families were confidently identified. Our dataset extends the DNA barcode library of Sub-Antarctic and Antarctic fish species and provides a foundation for developing an enhanced identification guide for larval fish to be used by observers on board krill fishing vessels. Phylogenetic relationships were inferred from two commonly used barcode markers, the mitochondrial cox1 and the non-coding control region. We observed clear phylogenetic relationships, highlighting coherent placements of notothenioids, myctophids, Aulopiformes, Gadiformes and Zoarcoidei. The results suggest a discrepancy between observer-based and genetic identifications, with 20.6% of records representing misidentifications in the fishing seasons 2021/2022 and 2022/2023. Graphical Abstract Graphical abstract: illustrated by ©Louise Merquiol-Hatsya illustrations

Integrated onshore–offshore paleoseismic records show multiple slip styles on the plate interface, central Hikurangi subduction margin, Aotearoa New Zealand - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Alan R. Orpin; Stephanie E. Tickle; Lorna J. Strachan; Philip Barnes; Sian Camp; Monique Mckeown; Emily Twort (Quaternary Science Reviews, 2024)

Maternal PFOS exposure affects offspring development in Nrf2-dependent and independent ways in zebrafish (Danio rerio) - Marjorie Marin; Kate M. Annunziato; Madeline C. Tompach; Wenle Liang; Sarah M. Zahn; Sida Li; Jeffery Doherty; Jonghwa Lee; John M. Clark; Yeonhwa Park; Alicia R. Timme-Laragy (Aquatic Toxicology, 2024)

Do plants matter?: Determining what drives variation in urban rain garden performance - Robyn Dudrick; Margaret Hoffman; Jalayna Antoine; Kate Austin; Laura Bedoya; Shirley Clark; Hannah Dean; Ann Medina; Sybil G. Gotsch (Ecological Engineering, 2024)

A ∼200-year relative sea-level reconstruction from the Wellington region (New Zealand) reveals insights into vertical land movement trends - Daniel J. King; Rewi M. Newnham; Andrew B.H. Rees; Kate J. Clark; Ed Garrett; W. Roland Gehrels; Timothy R. Naish; Richard H. Levy (Marine Geology, 2024)

GWAS using low-pass whole genome sequence reveals a novel locus in canine congenital idiopathic megaesophagus - Sarah M. Bell; Jacquelyn M. Evans; Elizabeth A. Greif; Kate L. Tsai; Steven G. Friedenberg; Leigh Anne Clark (Mammalian Genome, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

An integrated proximal-distal radiocarbon dating approach provides improved age constraints for a key Holocene tephra isochron - Charlotte O. Pizer; Jamie D. Howarth; Kate J. Clark; Colin J.N. Wilson; Stephanie E. Tickle; Jenni L. Hopkins; Jenny A. Dahl (Quaternary Science Reviews, 2023)

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Tsunami runup and tide-gauge observations from the 14 November 2016 M7.8 Kaikōura earthquake, New Zealand - William Power; Kate Clark; Darren N. King; Jose Borrero; Jamie Howarth; Emily M. Lane; Derek Goring; James Goff; Catherine Chagué-Goff; James Williams; Catherine Reid; Colin Whittaker; et al. (Pure and Applied Geophysics, 2017)

Optic radiation structure and anatomy in the normally developing brain determined using diffusion MRI and tractography - Michael Dayan; Monica Munoz; Sebastian Jentschke; Martin J. Chadwick; Janine M. Cooper; Kate Riney; Faraneh Vargha-Khadem; Chris A. Clark (Brain Structure and Function, 2015)

Earthquake and Tsunami Potential of the Hikurangi Subduction Thrust, New Zealand: Insights from Paleoseismology, GPS, and Tsunami Modeling - Laura Wallace; Ursula Cochran; William Power; Kate Clark (Oceanography, 2014)

Alleles of the major histocompatibility complex play a role in the pathogenesis of pancreatic acinar atrophy in dogs - Kate L. Tsai; Alison N. Starr-Moss; Gopalakrishnan M. Venkataraman; Christopher Robinson; Lorna J. Kennedy; Jörg M. Steiner; Leigh Anne Clark (Immunogenetics, 2013)

A Unique Interactive Cognitive Behavioral Training Program for Front-Line Cancer Care Professionals - Karen Clark; Paul Greene; Kate DuHamel; Matthew Loscalzo; Marcia Grant; Kim Glazier; William Redd (Journal of Cancer Education, 2012)

Genome-wide association studies for multiple diseases of the German Shepherd Dog - Kate L. Tsai; Rooksana E. Noorai; Alison N. Starr-Moss; Pascale Quignon; Caitlin J. Rinz; Elaine A. Ostrander; Jörg M. Steiner; Keith E. Murphy; Leigh Anne Clark (Mammalian Genome, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Understanding hereditary diseases using the dog and human as companion model systems - Kate L. Tsai; Leigh Anne Clark; Keith E. Murphy (Mammalian Genome, 2007)